Health and environmental risk assessment - Ricci, Paolo F.; Rowe, M. D. (Michael D.) (Pergamon Press, 1985)
Process and input-output analysis have emerged as the two principal methods of analyzing health risks of energy technologies. This book describes applications and differences between these two methods with discussions of sources or error and uncertainty, data limitations and some solutions to common problems. Its goals are to provide understanding of the strengths and weaknesses of the methods and to provide a basis for standardizing risk assessment for energy policy analysis. Sections of the book describe risk analysis and develop issues common to both the process and input-output methods, de.